2016
DOI: 10.4103/1735-1995.187256
|View full text |Cite
|
Sign up to set email alerts
|

Where does magnetic resonance imaging stand in the diagnosis of knee injuries?

Abstract: Background:The aim of this study was to determine the diagnostic value of magnetic resonance imaging (MRI) in the diagnosis of knee injuries.Materials and Methods:Ninety-eight consecutive patients were enrolled in the study. In all patients, MRI and arthroscopy were performed and the results were compared.Results:MRI was most sensitive in the detection of medial meniscus injuries, and the highest specificity and negative predictive value (NPV) were found in the detection of posterior cruciate ligament injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is the primary diagnostic imaging tool for the identification of meniscal lesions [11, 17]. It has been shown that MRI has a good ability to diagnose preoperative primary meniscal tears [17, 22, 23, 33, 34]. A study by Thomas et al [28] showed that even with the diagnosis of primary meniscal lesion, MRI is not always indicated if the clinical examination strongly suggests pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the primary diagnostic imaging tool for the identification of meniscal lesions [11, 17]. It has been shown that MRI has a good ability to diagnose preoperative primary meniscal tears [17, 22, 23, 33, 34]. A study by Thomas et al [28] showed that even with the diagnosis of primary meniscal lesion, MRI is not always indicated if the clinical examination strongly suggests pathology.…”
Section: Introductionmentioning
confidence: 99%